Five little monkeys reading in bed - Christelow, Eileen (Boston, Mass Houghton Mifflin & Company, 2011)
Mama has said it is time for "Lights out! Sweet dreams! No more reading in bed," but her five little monkeys cannot resist reading just a few more books to one another.
Keywords: Books and reading; Bedtime; Monkeys; Mother and child; Conduct of life; Stories in rhyme; Fiction; Juvenile works